2003
DOI: 10.1074/jbc.m301544200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Human Rad9 Is Required for Genotoxin-activated Checkpoint Signaling

Abstract: Rad9, a key component of genotoxin-activated checkpoint signaling pathways, associates with Hus1 and Rad1 in a heterotrimeric complex (the 9-1-1 complex). Rad9 is inducibly and constitutively phosphorylated. However, the role of Rad9 phosphorylation is unknown. Here we identified nine phosphorylation sites, all of which lie in the carboxyl-terminal 119-amino acid Rad9 tail and examined the role of phosphorylation in genotoxin-triggered checkpoint activation. Rad9 mutants lacking a Ser-272 phosphorylation site,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
152
1
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 113 publications
(165 citation statements)
references
References 57 publications
(53 reference statements)
9
152
1
3
Order By: Relevance
“…However, as shown here, Hus1 deficient cells show increased sensitivity to IR-induced killing when using the clonogenic assay that measures reproductive ability. These results support the model that Hus1 associates with Rad1 and Rad9 as a 9-1-1 complex to respond to IR-induced DNA damage because Rad9 deficient cells are hypersensitive to IR-induced killing (Roos-Mattjus et al, 2003;Hopkins et al, 2004). IRinduced DNA double strands breaks (DSBs) are the most severe threat for cell survival.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, as shown here, Hus1 deficient cells show increased sensitivity to IR-induced killing when using the clonogenic assay that measures reproductive ability. These results support the model that Hus1 associates with Rad1 and Rad9 as a 9-1-1 complex to respond to IR-induced DNA damage because Rad9 deficient cells are hypersensitive to IR-induced killing (Roos-Mattjus et al, 2003;Hopkins et al, 2004). IRinduced DNA double strands breaks (DSBs) are the most severe threat for cell survival.…”
Section: Introductionsupporting
confidence: 77%
“…Rad9 is involved in IRinduced DNA damage response and Rad9 deficient cells are hypersensitive to IR-induced killing (Roos-Mattjus et al, 2003;Hopkins et al, 2004). It is reasoned, then, that Hus1 should also affect the sensitivity of mammalian cells to IR-induced killing.…”
Section: Hus1 Deficient Cells Are Hypersensitive To Ir-induced Killingmentioning
confidence: 99%
“…The tail is heavily phosphorylated, with multiple sites having been identified (Chen et al 2001;St. Onge et al 2001, 2003Roos-Mattjus et al 2003). Although these sites are not required to generate the 9-1-1 clamp or for genotoxin-triggered loading of the clamp onto chromatin, a Rad9 mutant in which all the sites were simultaneously mutated could not facilitate Chk1 phosphorylation (Roos-Mattjus et al 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Onge et al 2001, 2003Roos-Mattjus et al 2003). Although these sites are not required to generate the 9-1-1 clamp or for genotoxin-triggered loading of the clamp onto chromatin, a Rad9 mutant in which all the sites were simultaneously mutated could not facilitate Chk1 phosphorylation (Roos-Mattjus et al 2003). Initial analyses of the phosphorylation sites revealed that Ser272, a site phosphorylated by ATM and ATR (Chen et al 2001), was not essential for Chk1 phosphorylation (Roos-Mattjus et al 2003).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation